School Principals' Understanding of the Independent Curriculum through Strengthening the Pancasila Student Profile - Rusdinal; Sulastri (Jurnal Pedagogi dan Pembelajaran, 2023)
This research is motivated by the need for more understanding of school principals regarding the independent curriculum and Strengthening the Pancasila Student Profile. This research aims to analyze the Project for Strengthening the Pancasila Student Profile, prepare an educational unit ecosystem, design the project, and process assessments. This type of research is quantitative. The research subjects were 63 school principals. Samples were taken using a purposive sampling technique. The instrument used in data collection was a Likert scale model. The technique used to analyze data is quantitative descriptive analysis. The research results show that understanding the Strengthening the Pancasila Student Profile includes understanding the Pancasila Student Project, preparing the education unit ecosystem, designing the Strengthening the Pancasila Student Profile Project, processing assessments, and reporting the results of the Strengthening the Pancasila Student Profile Project. The principal's understanding of Strengthening the Principal's Pancasila Student Profile is in the sufficient category. The research results indicate that the understanding of school principals regarding strengthening the Pancasila Student Profile still needs to be improved. A good understanding by the school principal regarding strengthening the character of the Pancasila Student Profile will have a better impact on the principal's learning leadership.